Modeling berth allocation and quay crane assignment considering QC driver cost and operating efficiency. (January 2021) - He, Junliang; Wang, Yu; Tan, Caimao; Yu, Hang
Abstract: Due to high labour costs and difference of QC driver's handling efficiency existing between day and night, factors concerning QC drivers can significantly impact the schedule of berth allocation and quay crane assignment. This paper tackles the berth allocation and quay crane assignment problem considering QC driver cost, difference of the operating efficiency and performance-related pay between day and night. How QC driver-related factors affect the schedules is analyzed, and the objective composition including QC driver cost is given. A mixed integer programming model with model acceleration algorithms is developed for the proposed problem, and a meta -heuristic framework including a three-stage algorithm is proposed for solving the problem. Numerical experiments are conducted to validate the effectiveness of the proposed model and performance of the meta -heuristic approach, leading to a multitude of managerial insights.